MENGHADIRKAN SOLUSI KETAHANAN PANGAN MELALUI PERTANIAN ORGANIK: PERSPEKTIF LITERATUR - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
Organic farming is increasingly recognised as a strategic solution for achieving sustainable food security in Indonesia. This system emphasises the use of natural materials without synthetic fertilisers and pesticides, thereby maintaining soil health, improving crop quality, and reducing negative impacts on the environment. Literature reviews indicate that organic farming not only produces safer and more nutritious food but also contributes to increased farmer income through higher product prices and growing market demand. However, the development of organic farming in Indonesia still faces various challenges, such as complex certification processes, limited farmer knowledge, and uneven market access. Therefore, policy support, education, and technological innovation are needed to enable organic farming to develop optimally and play a greater role in achieving healthy, self-reliant, and sustainable national food security.